Analisis Alih Kode Dalam Novel “Dear Allah” Karya Diana Febi - Devina Damayanti; Ita Kurnia; Nerina Tita Rahmadani (Institut Nalanda, 2023)
This research examines the form of code switching and code mixing in the novel